Sleep Strategies of Night-Shift Nurses on Days Off: Which Ones are Most Adaptive? - Petrov, Megan E.; Clark, C. Brendan; Molzof, Hylton E.; Johnson, Russell L.; Cropsey, Karen L.; Gamble, Karen L. (Frontiers in Neurology, 2014)
Objectives: To determine the off-shift sleep strategies of bi-ethnic night shift nurses, the relationship between these sleep strategies and adaptation to shift work, and identify the participant-level characteristics associated with a given sleep strategy. Methods: African American and non-Hispanic White female, night shift nurses from an academic hospital were recruited to complete a survey on sleep-wake patterns (n = 213). Participants completed the Standard Shiftwork Index and the Biological Clocks Questionnaire to determine sleep strategies and adaptation to night shift work. In addition, chronotype was determined quantitatively with a modified version of the Munich ChronoType Questionnaire. Most participants worked approximately three consecutive 12-hour night shifts followed by several days off. Results: Five sleep strategies used on days off were identified: a) Night Stay, b) Nap Proxy, c) Switch Sleeper, d) No Sleep, and e) Incomplete Switcher. Nap Proxy and No Sleep types were associated with poorer adaptation to night shift work. The Switch Sleeper and Incomplete Switcher types were identified as more adaptive strategies that were associated with less sleep disturbance, a later chronotype, and less cardiovascular problems. Conclusions: Behavioral sleep strategies are related to adaptation to a typical night-shift schedule among hospital nurses. Nurses are crucial to the safety and well-being of their patients. Therefore, adoption of more adaptive sleep strategies may reduce sleep/wake dysregulation in this population, and improve cardiovascular outcomes.